Optimalisasi Manajemen Publikasi Ilmiah melalui Pelatihan Open Journal System (OJS) pada Akademi Perhotelan Tunas Indonesia - Damayanti, Devi; Pratama, Firman (Universitas Pamulang, 2025)
The Open Journal Systems (OJS) training at Akademi Perhotelan Tunas Indonesia was conducted to enhance the capacity of journal managers in organizing scientific publications in a digital, structured, and standardized manner. The training methods included lectures, presentations, system demonstrations, hands-on training, case studies, and interactive discussions. The results showed that participants improved their understanding and practical skills in using OJS—from submission and review to editing and publication. Evaluation and feedback indicated that the training was relevant, applicable, and supported the strengthening of journal governance in vocational education settings. This training is expected to serve as the foundation for developing a professional and accredited scientific journal at the institution. Keywords: Training, Open Journal Systems, scientific publication, vocational education, journal management